Relationship between quality of life and restless legs syndrome among a community-dwelling population in Japan - Kubo K (Dove Medical Press, 2016)
Kazutoshi Kubo,1 Norio Sugawara,1,2 Ayako Kaneda,1 Ippei Takahashi,3 Kazuhiko Nakamura,1 Shigeyuki Nakaji,3 Norio Yasui-Furukori1 1Department of Neuropsychiatry, Hirosaki University School of Medicine, Hirosaki, 2Department of Psychiatry, Aomori Prefectural Center for Mental Health and Welfare, Aomori, 3Department of Social Medicine, Hirosaki University School of Medicine, Hirosaki, Japan Objectives: Restless legs syndrome (RLS) is a sensorimotor disturbance that causes the production of impulses and dysesthesia and makes the patients feel as though they must move their lower extremities. Because the symptoms of RLS in the lower limbs tend to develop at night, RLS could cause sleep disorders. We investigated an association between the symptoms of RLS and the health-related quality of life among community-dwelling individuals in Japan. Methods: In this cross-sectional survey, we enrolled 985 volunteers who participated in the Iwaki Health Promotion Project in 2013. The symptoms of RLS were evaluated by the criteria of the International Restless Legs Syndrome Study Group. The assessments included an interview to obtain sociodemographic data, the second version of the Short Form Health Survey, the Center for Epidemiological Studies Depression scale, and the Pittsburgh Sleep Quality Index. A multiple regression analysis was used to assess the relationship between the symptoms of RLS and subscores of the Short Form Health Survey, Version 2. Results: The overall prevalence of RLS in our participants was 1.0%. We found a significant and negative association between symptoms of RLS and physical functioning, role – physical functioning, bodily pain, social functioning, and the physical composite summary score. Conclusion: After adjusting for confounders such as age, sex, and comorbidity, the burden of RLS appears to be mainly a physical problem. Impaired health-related quality of life among community individuals with RLS emphasizes the importance of screening for these symptoms and evaluating the need for treatment. Keywords: cross-sectional study, restless legs syndrome, quality of life, Japanese